2022
DOI: 10.1021/acsomega.1c06931
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity Studies of 3D-Printing Polyetheretherketone Substrates with Surface Growth of 2D TiO2/ZnO Rodlike Arrays

Abstract: Heterogeneous metal implants have been applied in clinical treatments of skeletal wounds, but their low antibacterial properties and the possibility of a release of metal ions may have harmful influences on the human body. Therefore, a polymer implant with low cost, high safety, an elastic modulus similar to that of human bone, and a good antibacterial property must be produced for orthopedic treatments. In this study, the surface of a 3D-printed polyetheretherketone (PEEK) disk was grown with ZnO/TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…To further verify the effect of buffer on the release of BSA@ZIF-8 NPs, we investigated the abovementioned release situation of BSA@ZIF-8 NPs in lactic acid and saline solution (Figure S9). It was found that the release rate and amount of BSA@ZIF-8 after incubation in pure lactic acid were higher than those in NaCl solution with lactic acid, which indicated that the concentration of hydrogen bonds in buffer solution was the key factor to determine the release of protein at the same pH value. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further verify the effect of buffer on the release of BSA@ZIF-8 NPs, we investigated the abovementioned release situation of BSA@ZIF-8 NPs in lactic acid and saline solution (Figure S9). It was found that the release rate and amount of BSA@ZIF-8 after incubation in pure lactic acid were higher than those in NaCl solution with lactic acid, which indicated that the concentration of hydrogen bonds in buffer solution was the key factor to determine the release of protein at the same pH value. , …”
Section: Resultsmentioning
confidence: 99%
“…It was found that the release rate and amount of BSA@ZIF-8 after incubation in pure lactic acid were higher than those in NaCl solution with lactic acid, which indicated that the concentration of hydrogen bonds in buffer solution was the key factor to determine the release of protein at the same pH value. 23 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…A chemical synthesis method was employed to cultivate zinc oxide (ZnO) nanorod arrays on FDM printed PEEK substrates as carriers of antibiotics (ampicillin or vancomycin), aiming to provide appropriate antibacterial characteristics to these samples ( Figure 7B ) ( Chen et al, 2019 ). To avoid the disintegration of ZnO rod-shaped arrays due to the acidic nature of attached antibiotics and to prevent cell cytotoxicity and repaid drug release caused by the release of metal ions, an additional procedure can be conducted to modify the ZnO rod-shaped arrays ( Figure 7C ) ( Lau et al, 2022 ). The 3D printed PEEK disks were covered with layers of TiO 2 on the surface of grown ZnO arrays using a chemical bath deposition technique to produce TiO 2 /ZnO/PEEK composites.…”
Section: Improved 3d Printed Peek For Bone Reconstructionmentioning
confidence: 99%
“…(C) Antibacterial activity of 3D-printing polyetheretherketone substrates with surface grown TiO 2 /ZnO rodlike arrays. Reproduced with permission ( Lau et al, 2022 ). Copyright 2022, The Authors.…”
Section: Improved 3d Printed Peek For Bone Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation